Smooth muscle-like tissues engineered with bone marrow stromal cells - Cho, SW; Kim, IK; Lim, SH; Kim, DI; Kang, SW; Kim, SH; Kim, YH; Lee, EY; Choi, CY; Kim, BS (ELSEVIER SCI LTD, 2004)
Bone marrow-derived cells have demonstrated the ability to differentiate into multiple mesenchymal cell lineages. Here we tested whether smooth muscle (SM)-like tissues can be created in vivo with bone marrow stromal cells (BMSCs). Cultured canine BMSCs, which expressed SM cell-specific markers including SM alpha-actin and SM myosin heavy chain, were seeded on three-dimensional, biodegradable polymer scaffolds and implanted into peritoneal cavity of athymic mice. The cell-scaffold constructs retrieved 4 weeks after implantation formed three-dimensional tissues. Inummohistochemical analyses showed that the tissue reconstructs expressed SM alpha-actin and SM myosin heavy chain. Masson's trichrome staining showed the presence of significant amounts of collagen in the tissue reconstructs. Cells labeled with a fluorescent tracer prior to implantation were still present in the tissue reconstructs 4 weeks after implantation. Non-seeded scaffolds (control groups) retrieved 4 weeks after implantation did not exhibit extensive tissue formation. This study demonstrates the potential of BMSCs as an alternative cell source for tissue engineering of SM. (C) 2003 Elsevier Ltd. All rights reserved.
Keywords: STEM-CELLS; DIFFERENTIATION; COLLAGEN; ACTIN